Association between the participation of the plastic surgery department and qualitative prognoses in severe trauma patients: A retrospective observational study. Issue 51 (23rd December 2022) - Lim, Nam Kyu; Kim, Sungyeon; Hee Yoon, Jae; Choi, Kyung-Hwa
Abstract : Catastrophic incidents would necessitate the intervention of multiple specializations with plastic surgery (PS) as an indispensable area of expertise. In view of PS, prognostic assessment of trauma patients should be focused on the qualitative value rather than mortality because plastic surgeons rarely handled patients' vital signs in actual. Thus, we explored the association between the involvement of the PS department and qualitative prognoses for severe trauma patients. From November 2014 to December 2019, we enrolled total 529 trauma patients with an injury severity score (ISS) over 15 points. We set the prognostic factors that the rate of admission in intensive care unit (ICU), total or ICU duration of hospitalization, post-discharge progress and disability diagnosis which were regarded as qualitative prognoses. The analysis was performed with logistic regression analysis or regression analysis adjusted for age, sex, past medical history, cause of trauma, and frequency of operation. Among total of 529 patients, 290 patients in PS group and 239 patients in non-PS group were analyzed. In both groups, the under-65-year ages and male patients were significantly predominant. The rate of going home showed 2.082 times higher in PS group than non-PS group after adjusting for covariates, while there was no significant difference in diagnosis of disability. Meanwhile, overall prognoses were highly correlated with either higher ISS or lower Glasgow Coma Scale (GCS). In conclusion, higher severity generally affected to the severe trauma patient's prognoses, and the PS treatment only contributes to discharge disposition to home.